New world solutions to old world problems: the growing reach of Latin American research = Soluciones del nuevo mundo para problemas del viejo mundo: el creciente alcance de la investigación latinoamericana - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2010)
Originally created to serve Latin America and the Caribbean, the International Center for Tropical Agriculture (CIAT) showed that agricultural research in tropical America is highly relevant to Africa and Asia. A steady stream of so-called “South-South” exchanges continues to this day, yielding significant benefits for farmers in Africa, Asia, and Latin America. A cassava pest in checkmate: One of the earliest examples involved biological control of the cassava mealybug, a pest of South American origin, which in the 1970s began causing serious damage to one of Africa’s most important staple foods. CIAT entomologists worked with colleagues at the International Institute of Tropical Agriculture (IITA) in search of the mealybug’s natural enemies in South America. The best candidate turned out to be a parasitic wasp and its release in 30 countries across Africa’s cassava belt led to effective control of the mealybug, generating economic benefits that exceeded the investment by a factor of nearly 150. We are now using our expertise in biological control to help farmers tackle cassava pest outbreaks in South East Asia.